2022
DOI: 10.3920/wmj2020.2676
|View full text |Cite
|
Sign up to set email alerts
|

Dietary exposure to mycotoxins of 1- and 2-year-old children from a Dutch Total Diet Study

Abstract: In 2017, a Total Diet Study was conducted in the Netherlands in which mycotoxins were analysed in foods and beverages consumed by 1- and 2-year-old children. These mycotoxins were aflatoxins, Alternaria toxins, citrinin, ergot alkaloids, fumonisins, ochratoxin A, patulin, sterigmatocystin, trichothecenes, and zearalenone. Long-term exposure was calculated by combining concentrations in foods and beverages with consumed amounts of these products. Analysed foods and beverages with a concentration below the detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…The exposure levels of the single mycotoxins can be found in Sprong et al [ 27 ] and Pustjens et al [ 26 ], with the exception of DAS and MON. The latter two mycotoxins were analysed in the TDS samples from Pustjens et al [ 26 ], but not reported in the that publication.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The exposure levels of the single mycotoxins can be found in Sprong et al [ 27 ] and Pustjens et al [ 26 ], with the exception of DAS and MON. The latter two mycotoxins were analysed in the TDS samples from Pustjens et al [ 26 ], but not reported in the that publication.…”
Section: Resultsmentioning
confidence: 99%
“…The exposure levels of the single mycotoxins can be found in Sprong et al [ 27 ] and Pustjens et al [ 26 ], with the exception of DAS and MON. The latter two mycotoxins were analysed in the TDS samples from Pustjens et al [ 26 ], but not reported in the that publication. As we had access to both datasets and calculations from the two TDSs that were previously published by our group, we were able to assess the combined risk of the mycotoxins in the respective assessment groups by combining all individual RPQs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations